Characterization of forced degradation products of toloxatone by LC-ESI-MS/MS - Robert Skibiński; Jakub Trawiński; Łukasz Komsta; Diana Murzec (Elsevier, 2018)
Forced degradation of toloxatone in solutions under basic, acidic, neutral, photo UV-VIS, photo UVC and oxidative stress conditions was investigated and structural elucidation of its degradation products was performed with the use of UHPLC system coupled ESI-Q-TOF mass spectrometer. Eight degradation products were found and their masses and formulas were obtained with high accuracy (0.09-3.79 ppm). The structure of unknown degradation products were elucidated from MS/MS fragmentation spectra of all analyzed compounds. Additionally, whole signals of decomposed substances were compared chemometrically. It was found that toloxatone is fragile towards basic hydrolysis, oxidative conditions and UVC irradiation. Finally, the toxicity of transformation products was computationally evaluated and compared in multivariate manner. Keywords: Q-TOF, Mass spectrometry, UHPLC, Photodegradation, Toxicity